Forest cover of Kibonge Forest in Kenya between 1974 and 2016 - Chirchir , Elizabeth (African Journal of Education,Science and Technology (AJEST), 2015)
This report outlines, describes and analyses the status of Kibonge forest for purposes of synthesizing and presenting information to be easily understood by policy makers and forest conservators. Data on national cover change and drivers is scarce thus constraining design and regional approach to policies and practices for sustainable forest management and use. This study aims at giving the forest cover using Landsat imageries. Data was collected between, July 2013 and July 2014. The status of the forest was established by taking, eight multi temporal Land sat imageries at intervals of 4 years from 1978 – 2016. The mappings were prepared while following six major steps: pre-processing satellite images, visual image interpretation, field data collection (ground truth), field data analysis, digital image classification and map accuracy assessment. Measurements were given as percentage cover. There was a general decrease (n=7, r = 0. 956, p< 0.001) in the size of Kibonge forest especially between 1989 and 2010, forest area decreased by 5.9 % similar to a decrease of Mt. Kenya forest during the same period. There was increase in cropland and grassland area by 11.08%, a strong indicator of human encroachment to the forest. There is need for forest protection to allow regeneration of indigenous species, reforestation and establishment of buffer zones made of exotic species between human settlement and the forest. Improved law enforcement of illegal logging, proper forest management, sufficient funding and the promotion of alternative human resources are the best measures to restore the forest canopy cover.